Effectiveness of cognitive therapy on reducing irrational beliefs of 12-14 Year old adolescents and 18-20 year old adolescents - Najafi, T.; Lea-Baranovich, D. (2010)
This study seeks to see whether there is a significant difference in the extent to which REBT reduces irrational beliefs between the two experimental groups: 12-14 year old adolescents and 18-20 year old adolescents? An experimental pre-test and post-test design was used in this research. The sample consisted of 32 Iranian female adolescents living in Kuala Lumpur. They were assigned in 4 groups randomly: one 12-14 year old group, one18-20 year old group; and 2 control groups. Participants took part in 10 Cognitive Therapy sessions. Results show that the treatment has been effective in both groups, but it has been more effective in the 12-14 year old group. Based on this study, the researcher recommends providing REBT psycho-educational programs in educational settings for adolescents who live in foreign countries. Also, it is recommended to integrate cognitive programming as part of classroom curriculum.